Evaluation of absorbent materials for use as ad hoc dry decontaminants during mass casualty incidents as part of the UK’s Initial Operational Response (IOR) - Kassouf, Nick (PLoS One, 2017)
The UK’s Initial Operational Response (IOR) is a revised process for the medical management of mass casualties potentially contaminated with hazardous materials. A critical element of the IOR is the introduction of immediate, on-scene disrobing and decontamination of casualties to limit the adverse health effects of exposure. Ad hoc cleansing of the skin with dry absorbent materials has previously been identified as a potential means of facilitating emergency decontamination. The purpose of this study was to evaluate the in vitro oil and water absorbency of a range of materials commonly found in the domestic and clinical environments and to determine the effectiveness of a small, but representative selection of such materials in skin decontamination, using an established ex vivo model. Five contaminants were used in the study: methyl salicylate, parathion, diethyl malonate, phorate and potassium cyanide. In vitro measurements of water and oil absorbency did not correlate with ex vivo measurements of skin decontamination. When measured ex vivo, dry decontamination was consistently more effective than a standard wet decontamination method (“rinse-wipe-rinse”) for removing liquid contaminants. However, dry decontamination was ineffective against particulate contamination. Collectively, these data confirm that absorbent materials such as wound dressings and tissue paper provide an effective, generic capability for emergency removal of liquid contaminants from the skin surface, but that wet decontamination should be used for non-liquid contaminants.